Not All Is Well in My Ancestors' Home: An Indigenous Theology of Internal Critique - Longkumer, Atola (The ecumenical review, 2010)
Indigenous communities are not of themselves holistic, and are not necessarily free from abuse of power. They are equally in need of internal reforms and emancipation from external forces of dominance and marginalization exist. Indigenous communities need an internal critique of people's experiences, particularly minorities and women. This thesis is set in the context of the Ao Naga Indigenous people of Northeast India.